Absolute configurations of phytotoxic inuloxins B and C based on experimental and computational analysis of chiroptical properties. (October 2016) - Evidente, Marco; Santoro, Ernesto; Petrovic, Ana G.; Cimmino, Alessio; Koshoubu, Jun; Evidente, Antonio; Berova, Nina; Superchi, Stefano
Abstract: The absolute configuration of phytotoxins inuloxins B and C, produced by Inula viscosa, and with potential herbicidal activity for the management of parasitic plants, has been determined by Time-dependent density functional theory computational prediction of electronic circular dichroism and optical rotatory dispersion spectra. The inuloxin B has been converted to its 5- O -acetyl derivative, which due to its more constrained conformational features facilitated the computational analysis of its chiroptical properties. The analysis based on experimental and computed data led to assignment of absolute configuration to naturally occurring (+)-inuloxin B and (−)-inuloxin C as (7 R, 8 R, 10 S, 11 S ) and (5 S, 7 S, 8 S, 10 S ), respectively. Graphical abstract: The absolute configuration of the sesquiterpenoid plant phytotoxins inuloxin B (+)-2 and inuloxin C (−)-3 was determined by the concerted TDDFT computational simulation of ECD and ORD spectra. Highlights: Absolute configuration assignment by ECD and ORD chiroptical methods. Fungal and plant sesquitepenoid phytotoxins. Application of more than a single chiroptical methodology.